Parental Involvement in the Learning Process at Dharma Wanita Gampangsejati Kindergarten: Pola Keterlibatan Orang Tua dalam Proses Pembelajaran Anak Usia Dini - Dewi Kusuma Ningrom; Evi Destiana (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Early childhood education emphasizes holistic development that requires collaboration between families and educational institutions. Specific Background In kindergarten contexts, parents are positioned as primary educators whose participation supports children’s emotional security, learning readiness, and adaptation to school environments. Knowledge Gap Despite policy recognition of parental involvement, empirical descriptions of structured parental participation within classroom learning activities at early childhood institutions remain limited. Aims This study aims to describe forms of parental involvement, supporting factors, and inhibiting factors in the learning process of early childhood at Dharma Wanita Gampangsejati Kindergarten. Results Using a qualitative descriptive approach with observations, interviews, and documentation, the findings show that parents are actively involved through classroom accompaniment during the initial school period, participation in parenting activities, preparation of learning media, provision of nutritious meals, and routine school support activities. Parental participation contributes to children’s comfort, emotional stability, independence, and enthusiasm for attending school, while parental work commitments constitute a major constraint, addressed through family member substitution. Novelty This study documents an institutionalized classroom-based parental accompaniment program during the early months of schooling as a contextual practice in early childhood education. Implications The findings underscore the importance of structured school–family collaboration models to support early childhood learning processes and inform policy and practice in kindergarten-level education. Highlights: Family Participation Is Integrated Into Daily Classroom and School Routines. Structured Accompaniment Supports Children’s Emotional Comfort and Learning Readiness. Flexible Substitution Mechanisms Address Parental Participation Constraints. Keywords: Parental Involvement, Early Childhood Education, Learning Process, Kindergarten, Qualitative Study